Pembuatan Landing Page Sebagai Media Promosi Tas Chunky Pada Kegiatan KKN Tematik Universitas YPPI Rembang - Muhammad Ilham Al Asrori; Abdul Mu’is; Wahyu Prasetyo Hariyadi; Syakur (Jurnal Ragam Pengabdian, 2025)
The advancement of information technology has significantly transformed various sectors, including the field of economic business. Technology has become a strategic tool to enhance business quality, particularly through digital marketing. In response to this development, the Thematic KKN (Community Service Program) of Universitas YPPI Rembang implemented the development of a landing page as a promotional platform for a local product, namely the Chunky bag. This program aimed to utilize digital tools to broaden market reach and increase product attractiveness among modern consumers. Through participatory collaboration with the PKK (Family Welfare Empowerment) group in Ngotet Village, students conducted knitting skill training and provided education on the use of social media and digital platforms as promotional tools. The creation of the landing page represented a tangible integration of community empowerment and technological innovation. It is expected that this activity can serve as an example of how technology can be effectively implemented to support the growth of creative village economies and contribute to the professional and sustainable development of local MSMEs.